The Effect of the Honey-mumford model on unrealistic of Unrealistic optimism Among University Students - Asst.lect. Bassem Azyz Muhamad Alwayly (Journal of College of Education, 2025)
The current  research aims to identify the effect of the Honey-mumford model of unrealistic optimism among university  students,The sample consisted of ( A) the experimental group that  was exposed to the Honey model and ( B) the control group .Ascale for unrealistic optimism was developed to measure the variable of interest the research tools were applied to the students totaling (60) male and(30)  female students Results showed the positive influence of the Honey  model in building cognitive frameworks and improving awareness to reduce unrealistic optimism Recommendations emphasize the need to adopt this model to enhance the skills of university students in managing and assessing their perceptions
Keywords: honey- mumford model unrealistic optimism